Avaliação ultrassonográfica da dinâmica folicular ovariana de jumenta (Equus asinus) durante o ciclo estral - Conceiçãeo, J. C. [UNESP]; Neto, L. M. Freitas; Filho, C. R. Aguiar; Araújo, G. H M [UNESP]; Oliveira, J. V.; Bartolomeu, C. C.; Oba, Eunice [UNESP]; Meira, Cezinande de [UNESP] (My University, 2009)
The ovarian activity was accessed by ultrasound throughout 10 estrous cycles from Jennies (Marchador Brasileira). Daily ultrasound examinations were performed and the dada was retrospectively studied based on daily identification of each follicle detected. Blood samples were collected every 24 hours from ovulation (D0) until the next identified ovulation. The follicles measuring 11mm were detected and their mean diameter was registered daily using an ovarian map and permitting a retrospective evaluation of the dada, which represented the follicular growth dynamics. One and two major follicular waves were detected in six (60%) and four (40%) cycles respectively from ten estrous cycles in the present study. The primary wave emergency and follicle deviation from the cycles observed during the present study with one major follicular wave occurred at day 10.2 ± 0.75 and at day14.1 ± 0.81 and for cycles with two major waves, those events occurred at 9.0 ± 2.0 and 14.0 ± 1.15 days after ovulation. The maximum diameter of the dominant follicle at the cycles with one and two follicular waves were 37.2 ± 3.35 mm and 37.3 ± 1.1, respectively. The mean intervals from two ovulations were 23.0 ± 1.79 and 22.3 ± 1.26 days when observed in cycles with one and two major follicular waves. The maximum diameter of the dominant follicle was slightly smaller when double ovulations were observed if compared with the single ovulations (P > 0.05). It can be concluded that wave emergency period is observed around 9.6 days of the estrous cycle and the occurrence of deviation can be observed on day 14 of the estrous cycle.
Ultrasound evaluation of ovarian follicular dynamics in jennies (equus asinus) during the estrous cycle
Keywords: Equidae; Follicular dynamics; Ovary; Equus asinus